Engineering current collectors for advanced alkali metal anodes: A review and perspective - Liang Hu; Jiaojiao Deng; Qinghua Liang; Junxiong Wu; Bingcheng Ge; Qiang Liu; Guohua Chen; Xiaoliang Yu (EcoMat, 2023)
Abstract Alkali metal batteries (AMBs) are promising next‐generation high‐density electrochemical energy storage systems. In addition, current collectors play important roles in enhancing their electrochemical performances. Thus, it is essential to have a critical review of the most recent advances in engineering the current collectors for high‐performance AMBs. In this review paper, the fundamentals of alkali metal deposition on current collectors will be introduced first. Then recent advances in the development of advanced metal and carbon‐based current collectors are examined for boosting the stability and cycle life of lithium metal batteries (LMBs) in terms of various strategies including 3D architectural design and functional modifications. Thereafter, the research progress in design of advanced current collectors will be analyzed for sodium/potassium metal batteries, especially the counterparts that do not follow the paradigms established in LMBs. Finally, the major challenges and key perspectives will be discussed for the future development of current collectors in AMBs.